Addiction, traumatic loss, and guilt: A case study resolving grief through psychodrama and sociometric connections. (February 2020) - Giacomucci, Scott
Highlights: Psychodrama offers a process for speaking directly to the deceased person in surplus reality and an opportunity for closure. Sociometry can help normalize the experience of loss while connecting with others in the group. Sometimes telling the story of loss is not enough. Many clients will need a more embodied and multi-dimensional experience in treatment in order to transform their grief. These sociometric processes provide a group facilitator with the tools needed to develop group cohesion, promote mutual aid, identify similarities between individuals, and enrich interpersonal relationships. A case study of a psychodrama scene is presented with clinical processing and discussion of the potential effectiveness of the psychodramatic method in working with grief and loss. Abstract: Traumatic loss, complicated grief, and addiction can be difficult and complicated clinical issues. Many clients share their losses, self-blame or feelings of being stuck in their grief. However, verbal processing is not always adequate to stimulate change. Experiential sociometry provides refined tools for promoting strength-based connections between group members around their experiences of loss. The surplus reality of psychodrama offers unique opportunities to renegotiate the relationship to a deceased loved-one and offer the possibility of closure through role reversal. This article outlines four types of sociometric processes for cultivating connections between group members – the spectrogram, step-in sociometry, locograms, and floor checks. These experiential sociometry tools can be used independently as group processes or as a structured warm-up to a psychodrama enactment. A scene from a psychodramatic vignette is offered depicting a case study of a client working through complicated grief in an addictions group psychotherapy context. Sociometric and psychodramatic theoretical considerations are presented in the context of short practice depictions presented throughout this article. Psychodramatic letter writing is also introduced as an alternative for time limited groups or clinicians without extensive psychodrama training.